Do patients consult their GP for sexual concerns? A cross sectional explorative study - Audun Vik; Mette Brekke (Taylor & Francis Group, 2017)
Objective: To explore how often general practitioners (GPs) deal with patients' sexual concerns, what kind of concerns are brought up and how the GPs deal with them. Design: Cross sectional observational study. Setting/subjects: 22 GPs in Southern Norway. Main outcome measures: The percentage of consultations dealing with sexual concerns during three consecutive working days, as registered by the GPs on a questionnaire. Results: Out of 1 117 consultations, 47 (4.2%) dealt with sexual concerns, varying from 1.6 to 10.9% of consultations. The concerns brought up varied widely, with erectile dysfunction and pain related to sexual activity in females as the largest groups. Concerns regarding sexual orientation, preferences or behavior were also dealt with, as were problems due to sexual assaults or rape. In 36 (76.6%) of the consultations, discussion of the problem and/or advice was the only action. Medication was prescribed in one third of the consultations. Patients' mean age was 46.7 years, with a span from 17 up to 75 years and 60% were female. We found no associations between GP characteristics and how frequently they dealt with sexual concerns. Conclusions: In around 4% of consultations, the GPs dealt with a wide variety of sexual concerns.